Sectors Matter! Exploring Mesoeconomics - Mann, Stefan (Springer Berlin Heidelberg, 2011)
Although all economic activities take place in sectors, economists often devote little attention to differences between and characteristics of sectors. This book tries to show that mesoeconomics, the economic exploration of sectors and groups, is a useful instrument of analysis between microeconomics (the analysis of markets) and macroeconomics (the analysis of economies). In order to do so, economists and social scientists from related disciplines and coming from Europe, Australia and Asia, demonstrate that sectors matter for economic development and the formation of societies. The book includes chapters with rigorous economic analysis, outlooks on economic history, and case studies in order to show the relevance of sectoral issues, this broad range of content making it likely the most comprehensive book on mesoeconomics to date.